The Role of Andrographis paniculata (Burm.f.) Wall. ex Nees in Drug Interactions - Jutiviboonsuk, Aranya (Siriraj Medical Journal, 2015)
Andrographis paniculata (Burm.f.) Wall. ex Nees, commonly known as Fa-tha-lai-jone is an herbal medicine in The National List of Essential Drugs A.D.2013. The aerial part of the plant is used for treatment of non-infectious diarrhea and common cold. A. paniculata extract and its major active component, andrograpolide, have various pharmacological activities. Therefore co-administration of A. paniculata with conventional drugs may cause unpleasant interactions. This article reviews the role of A. paniculata and its active component that influences drug interactions including the effect on phase I and phase II metabolizing enzymes as well as drug transporter protein. Furthermore the data of pharmacokinetic and pharmacodynamic interactions on some clinical drugs are also included. Keywords: Andrographis paniculata, andrographolide, cytochrome P450, herb-drug interaction